Novel actinobacteria discovery and biosystematics of bacteria from antarctic soils on Barrientos Island - Lee, Learn Han (2012)
The Antarctic, one of the most poorly explored areas on Earth has emerged as a prospective region for the discovery of novel bacteria and bioactive metabolites. A total of 17 soil samples were collected from different areas of Barrientos Island to determine the distribution of bacteria in the soil and the potential of soil bacteria (particularly Actinobacteria) in producing bioactive secondary metabolites. The Biolog EcoPlate system and RAPD both demonstrated that soils with different types of rookery and characteristics could affect the soil DNA sequences and soil microbial diversity. The PCR-DGGE used to study the diversity of bacteria, especially Actinobacteria successfully displayed the diverse types of bacteria found within the soil and also provided estimations of their densities. A total of 96 bacterial strains were isolated using 12 different types of isolation media, 39 strains from phylum Actinobacteria and 57 strains from phyum Proteobacteria. Tests for bioactive secondary metabolites were performed and a total of 15 and 14 isolates of Actinobacteria and Proteobacteria were bioactive. The novel strain, 39T was fully characterized by using the polyphasic approach and results showed that it have many differences from the other genera in the family Dermacoccaceae on the basis of phylogenetic, chemotaxonomic, phenotypic and signature nucleotide pattern of the 16S rRNA gene. Therefore, it is suggested that strain 39T be classified as a novel genus in the family Dermacoccaceae, as Barrientosiimonas gen. nov., the type species of which is Barrientosiimonas humi gen. nov., sp. nov. It is evident from this study that the soil of Barrientos Island is a rich source of taxonomically diverse bacteria, especially Actinobacteria. The wide distribution of these bacteria in the Antarctic implies that they are endemic and therefore the bio-prospecting of soil bacteria from a wide range of geographic locations like the Antarctic regions would be of great benefit.